AN ASSESSMENT OF LEXICAL SENSE RELATIONS BASED ON WORD ASSOCIATION TEST - Nekah, Seyyed Mohsen Asghari; Akhlaghi, Elahm; Ebrahimi, Shima (European Scientific Journal, ESJ, 2013)
The present study intends to investigate lexical sense relations through the application of linguistic knowledge, cognitive processes in colloquial speech and word association test. In a word association test, a list of words is presented to subjects, who is asked to respond with the first word that comes into their mind, and this gives information on the way knowledge structures in the human mind. To achieve this purpose, first, it has been needed to prepare appropriate words; therefore, 300 students of the faculty of letters and humanities have been asked to write the first word which comes to their mind. Totally, 3000 words have been assembled. 22 words, which have had the highest frequency, have been chosen among those words to be applied in the questionnaire. To achieve the aim of the research, 17 lexical relations have been proposed by the researchers. This study has convenience sampling with 110 subjects. It has been concluded that the lexical storage system is strongly dependent upon sense relations. Language speakers can radically alter the relation between words on the basis of their mental conceptions, although Attributive relation, Functional relation and Social-cultural relation had the most frequency in this research. Attributive relation, 25.9%; Functional relation, 17%; Social-cultural relation, 11.9%; Synonymy, 9%; Collocational relation, 8%; Place relation, 3.3%; Meronymy, 3%; Need relation, 1.4%; Instrumental relation, 1.3%; Semantic opposition, 1.1%; Material relation, 0.6%; Negative relation, 0.5%; Time relation, 0.4%; Causal relation, 0.3%; Hyponymy, 0.13%; Specific relation, 0.1% and Member-collection, 0.1% are frequencies of each relation.